TREATMENT OF PATHOLOGICAL CAVITIES OF THE LIVER BY MODERN SURGICAL METHODS - Ergashev Ulugbek Yusufjanovich; Mustafakulov Gaybulla Irisbaevich; Zokhirov Adkhamjon Rafiqovich; Malikov Nodir Muzaffar ugli; Gafurov Behzod Tohirovich (Scholar Express Journals, 2023)
The aim of the work is to improve the results of surgical treatment of patients with cavitary liver masses using ultrasonic percutaneous puncture-drainage interventions.
Keywords: interventions; surgical; patients